Improving the activity and thermostability of GH2 β‐glucuronidases via domain reassembly. Issue 5 (19th February 2021) - Liu, Mingzhu; Yu, Jing; Lv, Bo; Hou, Yuhui; Liu, Xinhe; Feng, Xudong; Li, Chun
Abstract: Glycoside hydrolase family 2 (GH2) enzymes are generally composed of three domains: TIM‐barrel domain (TIM), immunoglobulin‐like β‐sandwich domain (ISD), and sugar‐binding domain (SBD). The combination of these three domains yields multiple structural combinations with different properties. Theoretically, the drawbacks of a given GH2 fold may be circumvented by efficiently reassembling the three domains. However, very few successful cases have been reported. In this study, we used six GH2 β‐glucuronidases (GUSs) from bacteria, fungi, or humans as model enzymes and constructed a series of mutants by reassembling the domains from different GUSs. The mutants PGUS‐At, GUS‐PAA, and GUS‐PAP, with reassembled domains from fungal GUSs, showed improved expression levels, activity, and thermostability, respectively. Specifically, compared to the parental enzyme, the mutant PGUS‐At displayed 3.8 times higher expression, the mutant GUS‐PAA displayed 1.0 time higher catalytic efficiency ( k cat / K m ), and the mutant GUS‐PAP displayed 7.5 times higher thermostability at 65°C. Furthermore, two‐hybrid mutants, GUS‐AEA and GUS‐PEP, were constructed with the ISD from a bacterial GUS and SBD and TIM domain from fungal GUSs. GUS‐AEA and GUS‐PEP showed 30.4% and 23.0% higher thermostability than GUS‐PAP, respectively. Finally, molecular dynamics simulations were conducted to uncover the molecular reasons for the increased thermostability of the mutant. Abstract : This study constructed a series of variants with improved activity, thermostability and expression level by reassembling the three domains (SBD, ISD and TIM) from six GH2 β‐glucuronidases (GUSs) from bacteria, fungi, or humans. Molecular dynamics simulations were conducted to uncover the molecular reasons for the increased thermostability of the variant. The domain reassembly strategy proposed in this study can be easily extended to the engineering of other GHs.